ANALISIS TINGKAT KEPUASAN SISWA DAN MOTIVASI DALAM PEMBELAJARAN KELOMPOK (COOPERATIVE LEARNING) DAN KAITANNYA DENGAN HASIL BELAJAR AKUNTANSI DI SMKLABOR BINAAN FKIP UNRI PEKANBARU - Muhammad Yasir; Suarman Suarman; Gusnardi Gusnardi (PEKBIS, 2017)
The purpose of this study was to determine the relationship between the level ofstudent satisfaction and motivation in learning groups (cooperative learning) andlearning outcomes in relation to the accounting subjects. The method in thisresearch is quantitative.The population of this research is the students of class XIand XII Accounting Department of SMK Labor Binaan FKIP Riau University. Dataobtained by observing the teacher in class and distributing questionnaires to therespondents. Data were analyzed by using multiple correlation while the instrumentwas tested by using validity. Results from these studies showed that: (1) There aredifferences in the level of satisfaction of students in study groups on special classesand regular classes at SMK Labor Binaan FKIPRiau University. (2) There aredifferences in student motivation in learning groups at special classes and regularclasses at SMK Labor Binaan FKIP Riau University.(3) There is a significantrelationship between the level of student satisfaction with the learning outcomes ofthe accounting subjects in SMK Labor Binaan FKIP Riau University. (4) There is asignificant relationship between motivation and learning outcomes of the accountingsubjects in SMK Labor Binaan FKIP Riau University. (5) There are differences in thelevel of student satisfaction and motivation in relation to group learning and learningoutcomes of the accounting subjects in SMK Labor Binaan FKIP Riau University.From the above results, it can be concluded that there is a significant relationshipbetween the level of student satisfaction and motivation in learning groups(cooperative learning) in accounting subjects in SMK Labor Binaan FKIP RiauUniversity.